The ultimate survival guide - McNab, Chris (Amber Books, 2014)
The world is a hostile environment, capable of throwing the unexpected at you at any moment. Bringing together the knowledge gained by those who have learnt it the hard way, The Ultimate Survival Guide is the only book you will ever need